Investigating how Grade 10 Physical Science teachers help learners to make sense of concepts of electromagnetism using easily accessible materials in under-resourced schools - Samuel, Paulo (Rhodes University, Faculty of Education, Department of Education, 2017)
This study sought to explore teachers' perceptions and experiences of using easily accessible materials and how they might collaboratively develop learning and teaching support materials using easily accessible materials. The study explored three aspects. Firstly, the views, experiences and factors which influence grade 10 Physical Science teachers' perceptions and experiences of teaching the topic of electromagnetism. Secondly, to find out what teachers can do to improve teaching and learning of electromagnetism in grade 10 Physical Science using easily accessible materials. Thirdly, to look at what enables or constrains grade 10 Physical Science teachers in under-resourced schools when dealing with electromagnetism, from using easily accessible materials. A qualitative method approach was adopted, underpinned by an interpretive paradigm but using some quantitative methods as well. Within the interpretive paradigm a case study approach was used. The study was carried out in Swakopmund and Gobabis education circuits of the Erongo and Omaheke Regions respectively. Data were collected using questionnaires, lesson observations and stimulated-recall interviews. The data obtained were validated in two ways, firstly, by triangulation from different data gathering techniques, and secondly, validation was done by member checking of the transcripts. To make meaning from the data generated, Vygotsky's (1978) socio-cultural theory was used as a lens to analyse the data. The quantitative data generated were presented in figures, tables; whereas the qualitative data were coded inductively into descriptive texts to make meaning. It was found that teachers's perceptions and experiences are that the topic of electromagnetism is quite challenging. Teachers reported that their learners find it difficult to comprehend phenomena associated with electromagnetism, thus making it difficult for their learners to grasp concepts associated with it. Lack of resources to do practical activities in the topic of electromagnetism was found to be a major contributing factor to teaching and learning of this topic. The use of easily accessible materials among teachers was found to be very limited. Easily accessible locally sourced materials were found to have the potential to enable grade 10 Physical Science teachers to help learners to make sense of concepts of electromagnetism in under-resourced schools. In light of the above findings, the study recommends that science teachers should make use of easily accessible materials which can minimise their dependence on standard laboratory equipment which is unaffordable anyway by most schools.
Keywords: Uncatalogued